2001
DOI: 10.1128/jvi.75.1.513-521.2001
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Transformation and Coexpression of Bovine Papillomavirus Type 1 E5 and E7 Proteins

Abstract: Productively infected bovine fibropapillomas were examined for bovine papillomavirus type 1 (BPV-1) E7 localization. BPV-1 E7 was observed in the cytoplasm of basal and lower spinous epithelial cells, coexpressed in the cytoplasm of basal cells with the E5 oncoprotein. E7 was also observed in nucleoli throughout the basal and spinous layers but not in the granular cell layer. Ectopic expression of E7 in cultured epithelial cells gave rise to localization similar to that seen in productive fibropapillomas, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
35
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 40 publications
1
35
1
Order By: Relevance
“…In bovine warts, the BPV E5 protein is expressed in epidermal keratinocytes as well as in dermal ®broblasts (Bohl et al, 2001;Burnett et al, 1992). Moreover, the BPV E5 protein can cause tumorigenic transformation of established murine keratinocytes (Leptak et al, 1991).…”
Section: The Vacuolar H + -Atpase As a Target Of The Bpv E5 Proteinmentioning
confidence: 99%
“…In bovine warts, the BPV E5 protein is expressed in epidermal keratinocytes as well as in dermal ®broblasts (Bohl et al, 2001;Burnett et al, 1992). Moreover, the BPV E5 protein can cause tumorigenic transformation of established murine keratinocytes (Leptak et al, 1991).…”
Section: The Vacuolar H + -Atpase As a Target Of The Bpv E5 Proteinmentioning
confidence: 99%
“…However, its function in vivo is still unknown. Recent reports show E5 expression in both equine and bovine BPV-infected cancers (Bohl et al, 2001;Carr et al, 2001), suggesting a possible role of this viral protein in malignant transformation in vivo. A total of 36 BPV-positive (including pre-neoplastic lesions) and 10 BPV-negative tumours were analysed together with 15 BPV-positive and 10 BPV-negative normal mucosa samples.…”
mentioning
confidence: 99%
“…This correlation extends beyond the phylogenetic topology and pathology. In BPV-1 fibropapillomas, it has been shown that E5 and E7 co-localize within the cytoplasm of undifferentiated basal epithelial cells, and that this co-expression is the basis of cooperative transformation between E5 and an E7 lacking the pRB-binding motif (Bohl et al, 2001). …”
mentioning
confidence: 99%